Method to Determine the Delay Between Measurements in Two or More Spectrum Analyzers or Power Meters - C. Goncalves, Luis; F. da Cunha, Diogo (Recent Advances in Communications and Networking Technology, 2016)
The aim is to compute the time delay between the set of measurements in each of two or more Spectrum Analyzers using a linear relation between two dimensions (power and time). This method of time measurement implies to input in each Spectrum Analyzer two identical and synchronized Amplitude Shift Keying signals, each one modulated by a square wave of duty cycle of 50%. It is also valid with Direct Current. Instead of an input of an Amplitude Shift Keying signal (Radio Frequency /Microwaves) a square wave is input and the power is measured with a Direct Current power meter with trigger.
Keywords: trigger by hardware